PELATIHAN PEMBUATAN BRIKET DARI ARANG TEMPURUNG KELAPA DI KELURAHAN KOLONGAN SATU KOTA TOMOHON - Meytij J Rampe (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Training on the briquettes synthesis from coconut shell charcoal has been conducted. This training was aimed to study the effects starch agent in the from solution on structural growth of briquettes and its chemical properties and the effect of temperature (200-500 oC) on the characters of the briquettes. The product characteristics of briquettes showed thatthere was a change on the chemical properties of the raw material which has been sintered at 300 oC, at which briquettes was produced in this process. Synthesis process at 300 oC in the presence of starch gave carbon material briquettes.